Pengembangan Bahan Ajar Kitab Alala Berbasis CTL dalam Meningkatkan Motivasi Belajar - Fathoni Fathoni (Muróbbî: Jurnal Ilmu Pendidikan, 2020)
Sakinah family guidance in the form of counseling for families who are deep in trouble at BP4, should be implemented in order to create a sakinah family and avoid divorce in particular as well as improve the resolution of marriage cases at BP4 as an increase in the function of BP4 as a Marriage Advisory agency. The success rate of sakinah family coaching, which is shown in the success of reconciling clients, is still very minimal and less than optimal. Constraints faced in coaching sakinah families include the strong willingness of clients to divorce and institutions with minimal funding. As a suggestion, the results of the research include: the Ministry of Religion should provide special funds for the operation of the BP4 institution, increase the number of Koneselor experts from various fields and coordinate with the Court to direct it to BP4 before processing. As well as making efforts to increase public awareness such as socialization on the importance of improving the quality of marriage.